2001
DOI: 10.1017/s0142716401002041
|View full text |Cite
|
Sign up to set email alerts
|

Breadth and depth of vocabulary in relation to L1/L2 acquisition and frequency of input

Abstract: Two empirical studies set out to explore the relation between breadth and depth of word knowledge and to link these concepts with language acquisition and frequency of language input. In the first study, the breadth and depth of word knowledge of 50 Dutch monolingual and bilingual kindergartners were investigated using receptive vocabulary, description, and association tasks. The second study examined the relation between the probability of knowing a word and the input frequency of that word in 1,600 Dutch mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
193
3
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(245 citation statements)
references
References 22 publications
17
193
3
12
Order By: Relevance
“…Words are the primary carriers of meaning, and it is widely recognized that there is a strong relationship between the individual's vocabulary size and his/her general language proficiency (Vermeer, 2001;Zimmerman, 2005). Methods for learning vocabulary, then, are an important part of language learning.…”
Section: Introductionmentioning
confidence: 99%
“…Words are the primary carriers of meaning, and it is widely recognized that there is a strong relationship between the individual's vocabulary size and his/her general language proficiency (Vermeer, 2001;Zimmerman, 2005). Methods for learning vocabulary, then, are an important part of language learning.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also identified other important variables that affect the vocabulary learning outcomes including different instructions of target vocabulary (Maynard et al, 2010), the frequency and saliency of the target words (Ellis, 2002;Vermeer, 2001), the types of contextual clues for lexical inferencing (Ellis, 1994;Nassaji, 2003;Zahar, Cobb, & Spada, 2001), types of read-aloud texts (Bortnem, 2008;Brabham, Boyd, & Edgington, 2000;Elliott & Dupuis, 2002), and teachers' read-aloud styles (Brabham & Lynch-Brown, 2002;Teale & Martinez, 1996). This study is the first attempt to empirically explore and relate two major factors influencing EFL children's word learning from teachers' story read-aloud.…”
Section: Discussionmentioning
confidence: 99%
“…Language learners, teachers, and researchers agree that vocabulary is an essential element in the process of learning a language (Schmitt, 2008), because words are the primary conveyors of meaning (Vermeer, 2001) and thus carry the main information load in communication. As Wilkins (1972) states, "without grammar very little can be conveyed, without vocabulary nothing can be conveyed" (p. 111).…”
Section: Introductionmentioning
confidence: 99%